Prevalence of cigarette and waterpipe tobacco smoking among adults in three Eastern Mediterranean countries: a cross-sectional household survey - Ramzi G Salloum; Mohammed Jawad; Aya Mostafa; Yousef Khader; Ji-Hyun Lee; Rima Nakkash; Niveen M E Abu-Rmeileh; Ali Chalak; Ruba Abla (BMJ Open)
Objectives Tobacco smoking is on the rise in the Eastern Mediterranean region. In light of limited surveillance of smoking in the region, this study sought to understand the prevalence of cigarette and waterpipe smoking among adults and the factors associated with smoking in Lebanon, Jordan and Palestine (West Bank only).Design, setting and participants Household surveys were conducted with participants over the age of 18 in Lebanon (n=1680), Jordan (n=1925) and Palestine (n=1679) between June and August 2019. A multistage cluster sampling approach with probability-proportional-to-size random selection method was followed in the three countries.Primary and secondary outcome measures Gender-specific prevalence rates for cigarette and waterpipe smoking were estimated. Multivariable logistic regression was used to examine factors associated with current cigarette and waterpipe tobacco smoking.Results The prevalence of cigarette smoking among males and females respectively was 48.6% and 21.5% in Lebanon, 50.4% and 9.1% in Jordan, and 53.4% and 3.1% in Palestine. The prevalence of waterpipe smoking among males and females respectively was 32.7% and 46.2% in Lebanon, 13.4% and 7.8% in Jordan, and 18.0% and 7.9% in Palestine. Cigarette smokers were significantly (p<0.05) more likely to be male, younger and with lower educational attainment across the three countries. Waterpipe smokers were more likely to be young adults across the three countries (p<0.001). They were more likely to be male in Jordan and Palestine, and more likely to be female in Lebanon.Conclusions The high prevalence rates of smoking in Lebanon, Jordan and Palestine are concerning. Continued surveillance is key to monitor smoking patterns and inform stronger tobacco control measures.